Use of proton pump inhibitors in scandinavian children and adolescents: An observational study - Closs, Emilie Raaum; Mårild, Karl; Nielsen, Rasmus Gaardskær; Størdal, Ketil (Frontiers in Pediatrics, 2023)
Abstract Aims: To examine the use of proton pump inhibitors (PPIs) in Scandinavian children with focus on the geographical variation, temporal changes and possible contributing factors to observed changes. Methods: An observational population-based study of children and adolescents (1-17 years) in Norway, Sweden, and Denmark during the period 2007-2020. Information concerning dispensed PPIs was obtained from the national prescription databases of each country and presented as means per 1000 children for each country and calendar year in four age categories (1-4, 5-9, 10-13 and 14-17 years). Results: In 2007, the PPI use in children was similar across Scandinavian countries. An increased PPI use was observed in all countries during the study period, with gradually increasing differences between the countries. In general, Norway showed both the largest total increase and the largest increase in each age category compared to Sweden and Denmark. In 2020 Norwegian children showed, on average, a 59% higher PPI use compared to Swedish children and a more than double the overall dispensation rate than Denmark. In Denmark there was a 19% reduction in dispensed PPIs from 2015 to 2020. Conclusion: Despite being countries with similar health care systems and without indications of increased incidence of gastroesophageal reflux disease (GERD), we observed considerable geographical variation and temporal changes of PPI use in children. Although this study did not contain data on the indication for PPI use, these large differences across countries and time may indicate a current overtreatment.